The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1210/jc.2002-021953
|View full text |Cite
|
Sign up to set email alerts
|

Nonsupplemented Luteal Phase Characteristics after the Administration of Recombinant Human Chorionic Gonadotropin, Recombinant Luteinizing Hormone, or Gonadotropin-Releasing Hormone (GnRH) Agonist to Induce Final Oocyte Maturation inin VitroFertilization Patients after Ovarian Stimulation with Recombinant Follicle-Stimulating Hormone and GnRH Antagonist Cotreatment

Abstract: Replacing GnRH agonist cotreatment for the prevention of a premature rise in LH during ovarian stimulation for in vitro fertilization (IVF) by the late follicular phase administration of GnRH antagonist may render supplementation of the luteal phase redundant, because of the known rapid recovery of pituitary function after antagonist cessation. This randomized two-center study was performed to compare nonsupplemented luteal phase characteristics after three different strategies for inducing final oocyte matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
155
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(169 citation statements)
references
References 34 publications
8
155
0
6
Order By: Relevance
“…With reference to the ART, various mechanisms have been proposed to explain the luteal deficiency observed particularly in IVF cycles, although there is some controversy in the published literature [2][3][4][5][6]. Indeed, one can assume that multifollicular development and consequently the supraphysiological estradiol levels secreted by the multiple corpora lutea during the early luteal phase exert a negative feedback of the hypothalamicpituitary axis, inhibiting the LH release necessary for the corpus luteum function [7].…”
Section: Introductionmentioning
confidence: 99%
“…With reference to the ART, various mechanisms have been proposed to explain the luteal deficiency observed particularly in IVF cycles, although there is some controversy in the published literature [2][3][4][5][6]. Indeed, one can assume that multifollicular development and consequently the supraphysiological estradiol levels secreted by the multiple corpora lutea during the early luteal phase exert a negative feedback of the hypothalamicpituitary axis, inhibiting the LH release necessary for the corpus luteum function [7].…”
Section: Introductionmentioning
confidence: 99%
“…Abysmally low levels of luteal phase LH may be insufficient to promote endometrial maturation to support an early pregnancy. Endogenous LH secretion can be suppressed for as long as 10 days after GnRH agonist treatment [15,16]. In order to compensate the low levels, progesterone gel, intramuscular progesterone, and suppository forms of this steroid are used by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that GnRH affects the cellular physiologic changes in the ovary, and oocyte growth and ovulation (2,3). This GnRH effect on ovarian function is associated with apoptosis in the ovary (7,8), but the mechanism has not yet been defined.…”
Section: Discussionmentioning
confidence: 99%
“…This gonadotropin affects the gonads and associated organs (1). GnRH affects the ovary directly without involving the pituitary gland; specifically, GnRH influences physiologic changes in ovarian granulosa cells, ovarian growth, and ovulation (2,3). Because the half-life of GnRH secreted in hypothalamus is very short and GnRH is not detected in serum, the action of GnRH in the ovary was thought to be caused by GnRH synthesized within the ovary (4).…”
Section: Introductionmentioning
confidence: 99%